Assessment of numerical radiation models on the heat transfer of an aero-engine combustion chamber - Gamil, Abdelaziz A. A.; Nikolaidis, Theoklis; Lelaj, Indrit; Laskaridis, Panagiotis (Elsevier, 2020)
Thermal radiation is the most dominant type of heat transfer inside the combustion chamber, which can directly affect the temperature distributions at the combustor walls. This paper provides a comprehensive analysis of the effects of two radiation models on the flame and liner-walls temperatures. A combustion chamber used in the Rolls-Royce-RB-183 turbofan engine was examined in this study by integrating a solid combustor model with the numerical fluid domain. The results indicated that the implementation of radiation models shrinks the flame peak-temperature and altered temperature distribution across the liner. The Discrete Ordinates Method (DOM) estimated a 10% higher temperature at the front part of the liner compared to the non-radiation model and 15% less than the P-1 radiation method. After the dilution zone, the DOM and P-1 models estimated respectively 15% and 25% reduction in the liner temperature compared to the non-radiation combustor. The radiation models have also down predicted the flame temperature by 200 K and more than 200 K for DOM and P-1 case respectively. The results also showed that the emissivity value had minimal effects on the combustor temperature distribution. The DOM considered being more accurate to estimate the combustor wall and flow temperatures compared to the P-1 radiation method
Keywords: Spherical harmonics (P-1); Discrete ordinates method (DOM); Radiative heat transfer; Radiation models; CFD; Gas turbine combustion